Casablanca - Alison, Joan.; Bergman, Ingrid, 1915-1982.; Bogart, Humphrey, 1899-1957.; Burnett, Murray.; Curtiz, Michael, 1888-1962.; Edeson, Arthur, 1891-1970.; Epstein, Julius J., 1909-2000.; Epstein, Philip G.; Greenstreet, Sydney.; Henreid, Paul.; Koch, Howard.; Lorre, Peter.; et al. (Warner Home Video, 2003)
Set in World War II Morocco within a city filled with European refugees. A bitter nightclub owner helps his former lover and her Resistance-hero husband escape from the Nazis.